The Decline of Florida Torreya: An Endemic Conifer on the Edge of Extinction - Jason A. Smith; Aaron Trulock (EDIS, 2011)
FOR276, a 5-page fact sheet by Jason A. Smith and Aaron Trulock, suggests a new understanding of the cause of decline and discusses current efforts to assess the population and develop a recovery plan. Includes references. Published by the UF Department of School of Forest Resources and Conservation, November 2010.